Comparison of ST segment Changes in Lead aVR with in-Hospital Outcomes in Patients with First attack of Acute Inferior ST Segment Elevation Myocardial Infarction (Cardiovascular Journal, 2019)
Background: Inferior wall ST segment elevation myocardial infarction is considered to be at lower risk than anterior wall STEMI except in some cases. The aim of our study was to evaluate the relationships between on admission ST segment changes in lead aVR and short term in-hospital outcomes in acute isolated inferior myocardial infarction undergoing thrombolysis.Methods: Total 107 of first attack of inferior STEMI patients were included and all were thrombolysed by streptokinase. The sample population were divided into three groups based on the condition of ST segment in lead aVR on admission and in hospital outcomes were observed: Group –A: ST segment elevation ≥0.5 mm; Group –B: ST segment depression ≥0.5 mm; Group-C: Iso-electric ST segment.Results: 6.54% of study population had ST segment elevation in lead aVR, 53.27% had ST segment depression in lead aVR and 41.12% had isoelectric ST segment in lead aVR. During hospital stay mortality rates of patients of Group A, Group B and Group C were 33.3%, 5.3% and 4.5 % respectively; rates of cardiogenic shock were 33.3%, 8.8% and 2.3% respectively; heart failure rates were 50.0%, 15.8% and 4.5% respectively; rates of recurrent angina after thrombolysis were 66.7%, 33.3% and 6.8% respectively in three groups and the mean LVEF were 40.17, 48.61 and 52.50 respectively.Conclusion: The on admission-isoelectric ST segment in lead aVR in acute inferior myocardial infarction predicted better in-hospital outcomes in comparison to ST segment elevation and ST segment depression in aVR. On the other hand, ST segment elevation in lead aVR predicted worse in-hospital outcomes than ST segment depression in acute inferior myocardial infarction in spite of reperfusion by thrombolytic.Cardiovasc. j. 2019; 11(2): 123-128